Dimorphic Mechanisms of Fragility in Diabetes Mellitus: the Role of Reduced Collagen Fibril Deformation. (19th October 2022) - Wölfel, Eva M.; Schmidt, Felix N.; vom Scheidt, Annika; Siebels, Anna K.; Wulff, Birgit; Mushumba, Herbert; Ondruschka, Benjamin; Püschel, Klaus; Scheijen, Jean; Schalkwijk, Casper G.; Vettorazzi, Eik; Jähn‐Rickert, Katharina; et al.
ABSTRACT: Diabetes mellitus (DM) is an emerging metabolic disease, and the management of diabetic bone disease poses a serious challenge worldwide. Understanding the underlying mechanisms leading to high fracture risk in DM is hence of particular interest and urgently needed to allow for diagnosis and treatment optimization. In a case–control postmortem study, the whole 12th thoracic vertebra and cortical bone from the mid‐diaphysis of the femur from male individuals with type 1 diabetes mellitus (T1DM) ( n = 6; 61.3 ± 14.6 years), type 2 diabetes mellitus (T2DM) ( n = 11; 74.3 ± 7.9 years), and nondiabetic controls ( n = 18; 69.3 ± 11.5) were analyzed with clinical and ex situ imaging techniques to explore various bone quality indices. Cortical collagen fibril deformation was measured in a synchrotron setup to assess changes at the nanoscale during tensile testing until failure. In addition, matrix composition was analyzed including determination of cross‐linking and non‐crosslinking advanced glycation end‐products like pentosidine and carboxymethyl‐lysine. In T1DM, lower fibril deformation was accompanied by lower mineralization and more mature crystalline apatite. In T2DM, lower fibril deformation concurred with a lower elastic modulus and tendency to higher accumulation of non‐crosslinking advanced glycation end‐products. The observed lower collagen fibril deformation in diabetic bone may be linked to altered patterns mineral characteristics in T1DM and higher advanced glycation end‐product accumulation in T2DM. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).